Implementation of link and match program development through online practice handbook - Supriyadi, Agus; Rusmawati, Retno Danu; Hartono, Hartono (Technium Social Sciences Journal, 2022)
This study aims to develop an online internship guide for the Borg & Gall model as a link and match form for Class XI Alfamart Competency in Online Business and Marketing Skills at SMK Negeri 1 Boyolangu. The development model used is the Borg and Gall model. The results showed that the link and match model developed after validation was declared valid. The product in the form of an online internship guide is declared feasible because all aspects of learning are in a suitable category. The link and match model development through prakerin is declared effective because it has met the criteria. The study results met the validity requirements, and the data analysis of observations on the implementation of prakerin carried out by students, SMK, and DUDI showed that the development of the Borg and Gall model was feasible to develop. The analysis of student work-readiness results is in the high category, stating that students are ready to enter the workforce. Based on the results of the research obtained, it concluded that the development of the link and match model through the prakerin developed has met the categories of validity, practicality, and interest so that it is feasible to develop.